Functional consequence of myeloid ferritin heavy chain on acute and chronic effects of rhabdomyolysis-induced kidney injury - McCullough, Kayla R.; Akhter, Juheb; Taheri, Mauhaun J.; Traylor, Amie; Zmijewska, Anna A.; Verma, Vivek; Hudson, Matthew C.; Sachdeva, Abhishek; Erman, Elise N.; Moore, Kyle H.; George, James F.; Bolisetty, Subhashini (Frontiers in Medicine, 2022)
Acute kidney injury (AKI) is a serious complication of rhabdomyolysis that significantly impacts survival. Myoglobin released from the damaged muscle accumulates in the kidney, causing heme iron-mediated oxidative stress, tubular cell death and inflammation. In response to injury, myeloid cells, specifically neutrophils and macrophages, infiltrate the kidneys and mediate response to injury. Ferritin, comprised of ferritin light chain and ferritin heavy chain (FtH), is vital for intracellular iron handling. Given the dominant role of macrophages and heme-iron burden in the pathogenesis of rhabdomyolysis, we studied the functional role of myeloid ferritin heavy chain in rhabdomyolysis-induced acute kidney injury and subsequent fibrosis. Using two models of rhabdomyolysis induced AKI, we found that during the acute phase, myeloid FtH deletion did not impact rhabdomyolysis-induced kidney injury, cell death or cell proliferation, suggesting that tubular heme burden is the dominant injury mechanism. We also determined that, while the kidney architecture was markedly improved after 28 days, tubular casts persisted in the kidneys, suggesting sustained damage or incomplete recovery. We further showed that rhabdomyolysis resulted in an abundance of disparate intra-renal immune cell populations, such that myeloid populations dominated during the acute phase and lymphoid populations dominated in the chronic phase. Fibrotic remodeling was induced in both genotypes at 7 days post-injury but continued to progress only in wildtype mice. This was accompanied by an increase in expression of pro-fibrogenic and immunomodulatory proteins, such as transforming growth factor-, S100A8 and tumor necrosis factor-. Taken together, we found that while the initial injury response to heme burden was similar, myeloid FtH deficiency was associated with lesser interstitial fibrosis. Future studies are warranted to determine whether this differential fibrotic remodeling will render these animals more susceptible to a second AKI insult or progress to chronic kidney disease at an accelerated pace.